THE EXPLORATION OF DUOLINGO APPLICATION FOR VOCABULARY BUILDING OF PRE-SERVICE TEACHERS - Erizara, Betri Virga; Wijirahayu, Suciana (UICELL, 2023)
This study aims to explore the use of the Duolingo Application for English vocabulary building for Pre-service English teachers at a private University in Jakarta. It uses a quantitative approach by distributing questionnaires to these prospective teachers. The questionnaire is to obtain comprehensive information from the respondents. There are five main aspects. The first is the evaluation of the effectiveness of using the Duolingo App in their vocabulary building. Second, it is an assessment of the ease of using the Duolingo Application as a learning tool. Third, the features in the application are evaluated, which one is the most useful for Vocabulary Building. Fourth is responses about barriers or obstacles that may be encountered in using the application to enrich English vocabulary. Finally, it is about the proposed solutions to overcome the obstacles. Data collection is at the university environment, particularly among Pre-service teachers who have experience in using Duolingo. The data analysis will involve quantitative descriptive methods to present the findings descriptively and provide an in-depth picture of the extent of utilization of the Duolingo App for Vocabulary building. The result is to provide an overview of the extent of utilization of the Duolingo App specifically for vocabulary building. Keywords: Duolingo, Vocabulary building, Pre-service English teachers